Acute toxicity of azadirachtin to a teleost, Heteropneustes fossilis - doi: 10.4025/actascibiolsci.v34i2.9455 (Acta Scientiarum. Biological Sciences, 2011)
The acute static renewal test of a botanical pesticide - azadirachtin for the freshwater catfish, Heteropneustes fossilis has been performed to determine the LC50 values at different exposure period. The LC50 values at various exposure periods are 173.06 mg L-1 for 24h; 80.69 mg L-1 for 48h; 58.57 mg L-1 for 72h and 52.35 mg L-1 for 96h. The upper confidence limits were 196.87, 86.91, 79.20 and 70.04 mg L-1 for 24, 48, 72 and 96 h and lower confidence limits were 154.01, 74.24, 37.33 and 33.83 mg L-1, respectively. These results indicate that azadirachtin exposure to the fish caused toxic effects.